Effectiveness Of The Addition Of Chlorine {Ca(Ocl)2} In Reducing Coliform Bacteria On Waste Liquid Hospital Pku Muhammadiyah Surakarta - Salamatur Rohmah, Khamimatus (2016)
ABSTRACT Liquid waste containing coliform bacteria substances can affect humans and the environment. Total coliform bacteria based on the results of preliminary tests conducted at the hospitals of PKU Muhammadiyah Surakarta amounting to 2400 colony/100 ml. One way to do is to use the method of chlorination with chlorine. The purpose of this research is to know effectivenes of a dose of chlorine in reducing coliform bacteria liquid waste hospital PKU Muhammadiyah Surakarta. This type of research study true experiment with pretest-posttest design with control group. Processing using chlorine in with a dose of 1,5 gr/lt, 2 gr/lt, and 2,5 gr/lt with a method of slow manual stirring 40 rpm 15 minute. The number of samples being tasted as many as 12 liters with a sampling technique is determined by quota sampling. Average yield effectiveness of coliform bacteria level after treatment are 99,834%, 99,417% and 99,361%. Statistical tests used of One Way Anova obtained p-value 0,000 value, shows differences in the decline of coliform bacteria before and after treatment with effective doses 1,5 gr/lt. Keyword : the liquid waste hospital, coliform bacteria, chlorine